APPLICATION OF A NEW CLASS OF NANOCOMPOSITES IN THE ECOLOGICAL MANAGEMENT OF FORMATION WATERS AT THE BIBIHEYBAT OIL AND GAS FIELD - MAMMADOVA, Nazila (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. A new utilization technology has been developed to ensure the rational reuse of toxic formation waters extracted from the oil fields of Bibiheybat OGPD in secondary technological processes and to restore ecological balance. The study presents a comparative analysis of the environmental impact mechanisms of nanocomposites N-1, N-2, and N-4. Methods. Formation water samples collected from the receiving reservoirs of the Bibiheybat OGPD oil fields were treated with various nanocomposites to evaluate their effects. Additionally, oil samples taken from the surface of formation water were analyzed for changes in rheological parameters, and the primary contaminant-mechanical impurities were treated using nanocomposites from the N-series. Results. The proposed new utilization technology has proven to be both ecologically and economically efficient in increasing the effectiveness of reusing formation water in secondary technological processes and minimizing its environmental impact. Without requiring the installation of new facilities in old oil fields, a closed-loop water supply system can be established using either N-2 or N-4 nanocomposites, depending on geological conditions. Conclusions. According to the research findings, nanocomposites N-2 and N-4 alter the type of formation water, converting it from "acidic" to "alkaline". These composites also enhance the rheological properties of oil. Within the framework of environmental safety standards, a closed-loop, zero-waste water supply system utilizing nanocomposites N-2 or N-4 is proposed as an eco-technological scheme for preparing formation water to meet required conditions.